Technologies for the Formation of the Political Image of the Ruling Parliamentary Party in Social Networks and Blogs: on the Example of the All-Russian Political Party “United Russia” - D. A. Golubenko (Управленческое консультирование, 2024)
The relevance of the topic of the article is that political parties in the information society inevitably use technologies to form their image through the use of social networks. In particular, Russian political parties have been actively using these technologies for 14 years, but the specifics of the content of information and methods of forming parliamentary political party image, including the ruling one, have not been studied enough on the Russian Federation materials.The purpose of the study is to establish technologies for the political image of the ruling parliamentary party formation in social networks using the example of All-Russian political party “United Russia”. Mainly attention is paid to the period 2016–2024 due to the chronology of the presidential and parliamentary elections.The research methods are communicative and network approaches in political science, a comparative method of analysis that allows to identify the technological components of the formation of the political image of the “United Russia” party, to determine their development trends. The method of content analysis of pre-election statements of a political party, campaign videos in official communities on the social networks Telegram, VKontakte and on the YouTube platform, communication with the public on the personal pages of candidates was used to reveal the contradictions of constructing the image of the party.The results of the study are that initially the Internet in Russia began to be used mainly by opposition parties, since it better corresponded to the profile of their target groups. Now the Internet is a comprehensive platform for creating and broadcasting information about the activities of Russian political parties, forming an interactive, competitive environment for political communication.Conclusions — the degree of effectiveness of the use of various technological components in the formation of the political image of the “United Russia” party has been established. More than half of the party’s information flows come from large Internet portals of well-known news and analytical publications. The activity of the official party community in the social networks VKontakte and Telegram, their stylistic design are at the proper level: posts about the activities of the party or about events with the direct participation of the party are published at least 2–3 times a day, are positive in subject matter. The emphasis is on positive coverage of party projects. The YouTube platform is used less efficiently. Recommendations have been formulated for the “United Russia” party to improve the effectiveness of the use of social networks and blogs in election campaigns.